Inspiring Excellence: How Transformational Leadership Shapes Institutional Performance in Higher Education - Aziz, Abd; Rachman, Poppy; Zamilah, Ainun (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze transformational leadership in shaping institutional performance in higher education, based on Bernard M. Bass's perspective integrated with spiritual values and local wisdom. The approach used is a qualitative case study type, where data is collected through interviews, observations, and documentation. Data were analyzed using thematic analysis techniques based on the Miles and Huberman model, which allows the identification of key themes related to transformational leadership practices. The results of the study indicate that the application of transformational leadership that integrates cultural and spiritual values can increase the motivation and involvement of lecturers and staff while contributing to improved academic performance. Through five main dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, individualized consideration, and cultural-spiritual synergy, this study proves that this approach is able to encourage increased institutional performance in higher education. The implication of this study is the importance of considering the cultural and spiritual context in leadership practices in educational institutions. The integration of these values not only creates a harmonious academic environment but also strengthens innovation, collaboration, and engagement, thus supporting the achievement of institutional goals in a sustainable manner.